2010
DOI: 10.1007/s10526-010-9272-3
|View full text |Cite
|
Sign up to set email alerts
|

The negative effect of some selective insecticides on the functional response of a potential biological control agent, the spider Philodromus cespitum

Abstract: The impact of five selective insecticides on the functional response of a potential biological control agent, the spider Philodromus cespitum (Walckenaer) (Araneae: Philodromidae), was studied in the laboratory. This spider is the most abundant beneficial arthropod on trees in commercial orchards in central Europe. We expected that selective insecticides applied at the recommended doses would have no effect or a negligible effect on the spiders' performance. Our results showed that the mortality of spiders res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 49 publications
(59 reference statements)
4
25
1
3
Order By: Relevance
“…Acute mortality from spinosad in laboratory assessments on arachnid predators gave diverging results. Řezáč et al 51 found no significant mortality when the spider Philodromus cespitum (Walckenaer) was exposed to dried spinosad residues on filter paper (104 mg AI L −1 ), whereas 100% mortality was observed for Hibana futilis (Banks) when exposed to very low spinosad residues (5 × 10 −20 µg AI L −1 ) on filter paper for 24 h 52. High Araneus pretensis (Emerton) mortality was observed owing to the ingestion of prey treated with low spinosad rates (2.5–25% of the maximum recommended field rates) 53.…”
Section: Side Effects Of Spinosyns On Non Target Organisms Reported mentioning
confidence: 99%
“…Acute mortality from spinosad in laboratory assessments on arachnid predators gave diverging results. Řezáč et al 51 found no significant mortality when the spider Philodromus cespitum (Walckenaer) was exposed to dried spinosad residues on filter paper (104 mg AI L −1 ), whereas 100% mortality was observed for Hibana futilis (Banks) when exposed to very low spinosad residues (5 × 10 −20 µg AI L −1 ) on filter paper for 24 h 52. High Araneus pretensis (Emerton) mortality was observed owing to the ingestion of prey treated with low spinosad rates (2.5–25% of the maximum recommended field rates) 53.…”
Section: Side Effects Of Spinosyns On Non Target Organisms Reported mentioning
confidence: 99%
“…Pesticides were found to decrease prey capture efficiency in a number of different species: in the linyphiid Hylyphantes graminicola (Sundevall, 1830) after application of methamidophis;59 in the lycosid Pirata piratoides (Bösenberg & Strand, 1906) and the linyphiid U. insecticeps after buprofezin application;89, 90 in the araneid Alpaida veniliae (Keyserling, 1865) after glyphosate application;91 in the lycosid P. pseudoannulata after imidacloprid application;68 in another lycosid P. amentata following application of cypermethrin;82 in the philodromid P. cespitum after exposure to diflubenzuron, neem, spinosad and acetamiprid;92 in the two linyphiids Erigone atra Blackwall, 1833 and O. apicatus after fenvalerate spray;80 in the araneid Neoscona pratensis (Hentz, 1847) after spinosad application;93 and in the lycosid Pardosa sp. after λ‐cyhalothrin spray 56.…”
Section: Direct Effectsmentioning
confidence: 99%
“…Insecticides may cause the death of the natural enemies (lethal effects) or change several other features of their physiology and behaviour without killing the individuals (sublethal effects) (Desneux et al 2007;Řezáč et al 2010).…”
mentioning
confidence: 99%